2016
DOI: 10.1080/21645515.2016.1238537
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanism of peptides with a repeating hydrophobic and hydrophilic residue pattern on interleukin-10

Abstract: Interleukin 10 (IL-10) is a cytokine that is able to downregulate inflammation. Its overexpression is directly associated with the difficulty in the clearance of chronic viral infections, such as chronic hepatitis B, hepatitis C and HIV infection, and infection-related cancer. IL-10 signaling blockade has been proposed as a promising way of clearing chronic viral infection and preventing tumor growth in animal models. Recently, we have reported that peptides with a helical repeating pattern of hydrophobic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…They found that the PPC binding affinity was closer to the experimental value reported by Nantermet et al ( 2003 ). For immune disorders, studies on Janus kinases (Zhang W. et al, 2016 ; Wang J. L. et al, 2017 ), interleukin 10 cytokine (Ni et al, 2017 ), and receptor-related orphan receptor-gamma-t (Wang F. F. et al, 2015 ), were reported. For inflammatory disorders, targets such as COX-2 (Chaudhary and Aparoy, 2017 ), interleukin 6 (Verma R. et al, 2016 ), toll-like receptors (Shen et al, 2016 ), human leukocyte antigen (Kongkaew et al, 2015 ), chymase enzyme (Verma et al, 2017 ), tumor necrosis factor (Ivanisenko et al, 2014 ), and Nalp3 (Sahoo et al, 2014b ) were studied.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…They found that the PPC binding affinity was closer to the experimental value reported by Nantermet et al ( 2003 ). For immune disorders, studies on Janus kinases (Zhang W. et al, 2016 ; Wang J. L. et al, 2017 ), interleukin 10 cytokine (Ni et al, 2017 ), and receptor-related orphan receptor-gamma-t (Wang F. F. et al, 2015 ), were reported. For inflammatory disorders, targets such as COX-2 (Chaudhary and Aparoy, 2017 ), interleukin 6 (Verma R. et al, 2016 ), toll-like receptors (Shen et al, 2016 ), human leukocyte antigen (Kongkaew et al, 2015 ), chymase enzyme (Verma et al, 2017 ), tumor necrosis factor (Ivanisenko et al, 2014 ), and Nalp3 (Sahoo et al, 2014b ) were studied.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…46 Recently, two peptides designed through computer modelling have been shown to inhibit IL-10 mediated signaling both in vitro and in vivo. [47][48][49] Temporally blocking IL-10 signaling at the time of immunization in mice does not cause an excessive inflammatory response. 50 These results argue that imiquimod may achieve better efficacy against genital warts if used together with an IL-10 inhibitor.…”
Section: Imiquimodmentioning
confidence: 99%
“…11 Vaccination with simultaneous IL-10 signaling blockade better inhibits tumor growth Immunization and simultaneously blocking IL-10 using IL-10 receptor monoclonal antibodies drastically increase vaccineinduced antigen-specific CD8 + T cell responses, regardless the immunogen is composed of virus-like particles, peptides, soluble antigens, or nucleotides (Table 1). 10,[18][19][20] The enhanced vaccineinduced T cell responses can also be achieved by using soluble IL-10 receptor, 21 peptide-based IL-10 receptor antagonist, 22,43 or oligonucleotides. 23 Subcutaneous administration of anti-IL-10 receptor antibodies together with a vaccine, instead of intraperitoneal injection of anti-IL-10 antibodies, also elicits stronger antigen-specific CD8 + T cell responses, yet at a much lower magnitude.…”
Section: Introductionmentioning
confidence: 99%